Identification and analysis of the driving factors for product modularity by Interpretive Structural Modelling - Shamsuzzoha, Ahm; Piya, Sujan (Brazilian Journal of Operations & Production Management, 2020)
Goal: The purpose of this study is to identify the driving factors that affects modular product design and development and to determine the contextual relationships between the identified factors. Design / Methodology / Approach: This research study adopted both qualitative and quantitative methodologies. In qualitative part, an extensive literature review is conducted along with interviews with the experts experienced in product design and development in order to identify and sorted out the driving factors for product modularity. In quantitative part, all the identified factors were analyzed through Interpretive Structural Modeling (ISM) method. MICMAC (Matrice d’Impacts Croisés Multiplication Appliquéeáun Classement (cross-impact matrix multiplication applied to classification) analysis is carried out to determine the relative driving and dependency power of the factors. Results: The contribution of this paper is the identification of the factors associated with developing a modular product. Through the use of ISM diagraph, the identified factors were clustered into different layers based on their driving and dependency characteristics. The ISM diagram also presented the relationship between one factor over others and the reason for such relationship. Such a diagram offers decision maker better visibility on the factor that they need to consider or strategy they need to implement to improve their modular product design and development architecture. The results from this research study encompass organizational managers for handling multiple design views, controlling design related interfaces and ranking the status and progress of product modularity and design completeness. Practical implications: The study outcomes support product designers to optimize their product development processes, especially to develop modular products. The presented methodology can be used extensively used by the product designers/planners/managers to find the driving factors related to modular product design and development. Originality / Value: The originality of this research study is to deploy the ISM approach, which can be used by the organizational managers and/or product designers to plan product development strategies. Such strategies help to them to make necessary decisions on resources allocations. Limitations of the investigation: The outcomes from this research may not be generalize sufficiently due to subjectivity of the interviewers.